Big Data in Electronic Health System and its Challenges - Aranya Nath, Kodukula Venkata Lakshmi Priyadarshini, Poushali Das, Antara Paral, Gautami Chakravarty, Naisargika Mishra (Mathematical Statistician and Engineering Applications, 2022)
During the 18th Century, where no Digitalization was there in any sector, the paper-pen-based data method, also referred to as the traditional method, was followed. From that perennial moment until today, science has flourished into various revolutions in every sector. The health sector is one of the most significant areas with a considerable level of intervention. Health care, which is inextricably related to life in general, has exhibited increasing reliance on advancing Technology, which has taken the lead in the name of a Digital Revolution in the health sector. The authors, through this chapter, seek to discuss the same and its link with Information Technology and Data Privacy guidelines in a descriptive manner. The Study will be started by the overview of the Technology used in the health care industry to the present techniques prominently used by doctors and physicians worldwide while we are in a pandemic situation. It would help the readers understand the revolution since its known significant inception. As the Covid-19 pandemic hit, the medical field triggered innovation. On the other hand, after the advent of Technology in the Healthcare sector, most of the Healthcare Data has been digitized, which refers to Electronic Health Records in the Healthcare Information system; it will discuss IPR management and Data Privacy Laws in this scenario.